No unless she skips a day or the parents don't Need her to work or they go on vacation
Step-by-step explanation:
well,
(y - 7)² = (y - 7)(y - 7)
remember how to multiply 2 expressions ?
you have to multiply every term of one expression with every term of the other expression and sum the results all up (incl. considering their individual signs, of course).
so, when we do the multiplication, we get
(y - 7)(y - 7) = y×y - 7×y - 7×y + (-7)×(-7) =
= y² - 14y + 49
and that is clearly different to y² - 49
FYI
y² - 49 is the result of
(y - 7)(y + 7)
because
y×y + 7×y - 7×y + (-7)(7) = y² - 49
Answer:
Compound interest = $365.4
Step-by-step explanation:
Given:
Amount borrowed = $6,000
Rate of interest = 3%
Number of year = year
Find:
Compound interest
Computation:
A = P[1+r]ⁿ
Amount after 2 year = 6,000[1 + 3%]²
Amount after 2 year = 6,000[1 + 0.03]²
Amount after 2 year = 6,000[1.03]²
Amount after 2 year = 6,000[1.0609]
Amount after 2 year = 6,365.4
Compound interest = Amount after 2 year - Amount borrowed
Compound interest = 6,365.4 - 6,000
Compound interest = $365.4
2t+3n=9 2(2)+3n=9
+5t-3n=5 (the 3n cancel out) 4+3n=9
7t=14 3n=5
t=2 n=5/3 or 1.67
Answer:
A.
Step-by-step explanation: